Residual stress measurement round robin on an electron beam welded joint between austenitic stainless steel 316L(N) and ferritic steel P91. (July 2017) - Javadi, Y.; Smith, M.C.; Abburi Venkata, K.; Naveed, N.; Forsey, A.N.; Francis, J.A.; Ainsworth, R.A.; Truman, C.E.; Smith, D.J.; Hosseinzadeh, F.; Gungor, S.; Bouchard, P.J.; et al.
Abstract: This paper is a research output of DMW-Creep project which is part of a national UK programme through the RCUK Energy programme and India's Department of Atomic Energy. The research is focussed on understanding the characteristics of welded joints between austenitic stainless steel and ferritic steel that are widely used in many nuclear power generating plants and petrochemical industries as well as conventional coal and gas-fired power systems. The members of the DMW-Creep project have undertaken parallel round robin activities measuring the residual stresses generated by a dissimilar metal weld (DMW) between AISI 316L(N) austenitic stainless steel and P91 ferritic-martensitic steel. Electron beam (EB) welding was employed to produce a single bead weld on a plate specimen and an additional smoothing pass (known cosmetic pass) was then introduced using a defocused beam. The welding residual stresses have been measured by five experimental methods including (I) neutron diffraction (ND), (II) X-Ray diffraction (XRD), (III) contour method (CM), (IV) incremental deep hole drilling (iDHD) and (V) incremental centre hole drilling (iCHD). The round robin measurements of weld residual stresses are compared in order to characterise surface and sub-surface residual stresses comprehensively. Graphical abstract: Highlights: A dissimilar metal weld (DMW) manufactured by electron beam welding was studied. The DMW specimen was made of a P91 and an AISI 316L(N) plate. Five independent experimental methods were used for residual stress measurement. All five measurement methods showed different uncertainties and potential errors. Deployment of independent techniques has strengthened the measurement reliability.